1981
DOI: 10.3354/meps004169
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Tolerance of Fertilized Eggs and Larval Survival in the Flsh Sillago sihama

Abstract: Salinity tolerance of fertilized eggs and larval survival of the fish Sillago siharna (Forskbl) were compared using fertilized eggs from induced and natural spawnings, and eggs from adults acclimated to lower salinities. Fertilized eggs at the blastomere stage were more sensitive to salinity change than those at other development stages. Fertilized eggs from natural spawning were more tolerant to salinity change than those from induced spawning. Fertilized eggs from adults acclimated to lower salinities showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Also, there were more dead larvae at higher salinities (greater than 4OYw). Fish larvae of several species surviving well at lower salinities have been reported (Nakai, 1962;Sylvester et al, 1975;May, 1975;Hu & Liao, 1979, Lee et al, 1981. However, fewer larvae with straight bodies were found at the lower salinities (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Also, there were more dead larvae at higher salinities (greater than 4OYw). Fish larvae of several species surviving well at lower salinities have been reported (Nakai, 1962;Sylvester et al, 1975;May, 1975;Hu & Liao, 1979, Lee et al, 1981. However, fewer larvae with straight bodies were found at the lower salinities (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Eggs, zygotes and juveniles of a marine clown fish (living in 35 PSU), showed normal development between 9 and 42 PSU (Dhaneesh et al., 2012). Adult salinity acclimation can also benefit egg development through plastic responses in euryhaline fishes (Kucera et al., 2002; Lee et al., 1981; May, 1974; Watanabe et al., 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this species have mainly focused on salinity tolerance [7], population dynamics [8], distinction of the genus Sillago [9], and phylogenetic relationships among the genus Sillago [10]. These studies found that S. sihama had tolerance to lower salinities [7], but with excessive exploitation, wild populations of S. sihama had been diminished in size and were low-aged [8]. The lack of genetic and genomic data for S. sihama has led to limited improvement in its breeding programs [11].…”
Section: Introductionmentioning
confidence: 99%